(untitled) (Journal of Academic Research, 2025)
This study was experimented to determine whether the dental cleaning methods used in the community were correct or not, and to determine the extent of the impact of these methods on the formation of bacterial plaque (dental), as well as the methods of cleaning and identifying bacterial plaque, tooth decay, and oral and dental care methods, and the study was conducted during the period During the period (12) 2016 until the end of the month (6) 2017 on a random sample that includes 50 people (25 male students, 25 female students), a clinical examination was conducted inside the dental clinic at the College of Medical Technology - Misurata, during the period from month (2) to month (3). The data that were recorded and analyzed in this study were obtained from the clinical detection of the Dental Plaque Index (D.P.I) in the mouth.